Influence of Different Cut-Off Values on the Diagnosis of Mild Cognitive Impairment in Parkinson's Disease - Inga Liepelt-Scarfone; Susanne Graeber; Anne Feseker; Gülsüm Baysal; Jana Godau; Alexandra Gaenslen; Walter Maetzler; Daniela Berg (Parkinson's Disease)
Comparable to Alzheimer's disease, mild cognitive impairment in Parkinson's disease (PD-MCI) is associated with an increased risk for dementia. However different definitions of PD-MCI may have varying predictive accuracy for dementia. In a cohort of 101 nondemented Parkinson patients who underwent neuropsychological testing, the frequency of PD-MCI subjects and PD-MCI subtypes (i.e., amnestic/nonamnestic) was determined by use of varying healthy population-based cut-off values. We also investigated the association between defined PD-MCI groups and ADL scales. Varying cut-off values for the definition of PD-MCI were found to affect frequency of PD-MCI subjects (9.9%–92.1%) and, maybe more important, lead to a “shift” of proportion of detected PD-MCI subtypes especially within the amnestic single-domain subtype. Models using a strict cut-off value were significantly associated with lower ADL scores. Thus, the use of defined cut-off values for the definition of PD-MCI is highly relevant for comparison purposes. Strict cut-off values may have a higher predictive value for dementia.